Efektivitas Komunikasi Website sebagai Media Informasi bagi Mahasiswa di Institut Agama Islam Tafaqquh Fiddin Dumai - Malika Azzahra; Suyanto Suyanto (MAN 4 Kota Pekanbaru, 2026)
The development of information technology encourages universities to utilize websites as a medium for communication and information delivery to students. Campus websites are expected to provide academic and administrative information quickly, easily accessible, and support communication between institutions and students. This study aims to measure the level of communication effectiveness of the IAITFDumai.ac.id website as an information medium for students of the Tafaqquh Fiddin Dumai Islamic Institute. This study uses a quantitative method with a descriptive approach. The research sample uses the Slovin formula so that 85 respondents are obtained who are active students. Data collection techniques are carried out through questionnaires with a Likert scale and documentation studies. Data collection was carried out from October to December 2025. Measurement of website communication effectiveness uses six indicators according to Kriyantono, namely content quality, ease of navigation, design and appearance, access speed, interactivity, and availability of online services. The results show that the effectiveness of website communication obtained a value of 80% which is included in the effective category. This study recommends increasing information updates and developing interactivity features so that the website can function more optimally as an information medium for students.